2019
DOI: 10.1186/s13063-019-3664-1
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of basket trials, umbrella trials, and platform trials: a landscape analysis of master protocols

Abstract: Background Master protocols, classified as basket trials, umbrella trials, and platform trials, are novel designs that investigate multiple hypotheses through concurrent sub-studies (e.g., multiple treatments or populations or that allow adding/removing arms during the trial), offering enhanced efficiency and a more ethical approach to trial evaluation. Despite the many advantages of these designs, they are infrequently used. Methods … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
260
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 288 publications
(266 citation statements)
references
References 60 publications
2
260
0
4
Order By: Relevance
“…For both basket trials and umbrella trials, they may be conducted with or without a control group (ie, randomized vs single‐arm nonrandomized designs). A landscape analysis recently showed that it is more common for umbrella trials to use a control group (n = 8 of 18 trials; 44.4%) than basket trials (n = 5 of 49 trials; 10.2%) . For umbrella trials, the control group may be placebo if there is no established care, or the existing standard of care for the disease being studied may be used for all of the subgroups.…”
Section: Characteristics Of Basket and Umbrella Trials: Eligibility Cmentioning
confidence: 99%
See 4 more Smart Citations
“…For both basket trials and umbrella trials, they may be conducted with or without a control group (ie, randomized vs single‐arm nonrandomized designs). A landscape analysis recently showed that it is more common for umbrella trials to use a control group (n = 8 of 18 trials; 44.4%) than basket trials (n = 5 of 49 trials; 10.2%) . For umbrella trials, the control group may be placebo if there is no established care, or the existing standard of care for the disease being studied may be used for all of the subgroups.…”
Section: Characteristics Of Basket and Umbrella Trials: Eligibility Cmentioning
confidence: 99%
“…With these rising interests and efforts toward precision care, it is vital to recognize the importance of biomarkers and how they are used to develop targeted therapies in clinical research . Notable methodological advancements that have recently been made toward biomarker‐guided clinical trials include the development of basket and umbrella design trials under the master protocol framework . A master protocol refers to a single, overarching design developed to evaluate multiple hypotheses with the general goal of improving efficiency through standardized trial procedures .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations